Spectrometric assessment of thyroid depth within the radioiodine test - Rink, T.; Bormuth, F.-J.; Schroth, H.-J.; Braun, S.; Zimny, M. (Nuklearmedizin - NuclearMedicine, 2005)
Aim of this study is the validation of a simple method for evaluating the depth of the target volume within the radioiodine test by analyzing the emitted iodine-131 energy spectrum. Patients, methods: In a total of 250 patients (102 with a solitary autonomous nodule, 66 with multifocal autonomy, 29 with disseminated autonomy, 46 with Graves’ disease, 6 for reducing goiter volume and 1 with only partly resectable papillary thyroid carcinoma), simultaneous uptake measurements in the Compton scatter (210 ±110 keV) and photopeak (364–45/+55 keV) windows were performed over one minute 24 hours after application of the 3 MBq test dose, with subsequent calculation of the respective count ratios. Measurements with a water-filled plastic neck phantom were carried out to perceive the relationship between these quotients and the average source depth and to get a calibration curve for calculating the depth of the target volume in the 250 patients for comparison with the sonographic reference data. Another calibration curve was obtained by evaluating the results of 125 randomly selected patient measurements to calculate the source depth in the other half of the group. Results: The phantom measurements revealed a highly significant correlation (r = 0,99) between the count ratios and the source depth. Using these calibration data, a good relationship (r = 0,81, average deviation 6 mm corresponding to 22%) between the spectrometric and the sonographic depths was obtained. When using the calibration curve resulting from the 125 patient measurements, the average deviation in the other half of the group was only 3 mm (12%). There was no difference between the disease groups. Conclusion: The described method allows an easy to use depth correction of the uptake measurements providing good results.
Keywords: Thyroid depth; iodine-131; photopeak; compton scatter; therapy planning